Thermodynamics of Adsorption of Iranian Weld Dye on Wool Fabric - Farizadeh, K.; Yazdanshenas, M.E.; Montazer, M.; Rashidi, A.; A. Malek, R.M. (Asian Journal of Chemistry, 2010)
The adsorption properties of the colouing matter from Weld have studied on wool fabric. In this study, the rate of dyeing at different temperature as well as the values of adsorption isotherm, affinity, entropy and enthalpy were estimated. The results show that with increasing of temperature the values of partition ratio and affinity decrease. The suitability of the adsorbent was tested by fitting the adsorption data with Langmuir isotherm. The effect of alum was also studied on adsorption isotherm and resulted that the adsorption isotherm is similar to without alum.